Multicultural Education in Private Universities Study at Nahdlatul Wathan University Mataram - Hilmi Sopian; Abdul Fattah (International Journal Labs, 2023)
This research is motivated by the existence of various kinds of ethnicities, religions, ethnicities, races and cultures in Indonesia. Diversity becomes a social force to build the strength of the nation. Conflicts that occur in several places in Indonesia as an illustration, how diversity can give birth to violence and defeat and unrest, especially in the world of education in universities. Therefore, multiculturalism education is important to be developed by UNW Mataram because UNW Mataram is a swatsa university located in the heart of the city of Mataram and was founded by national pahlwan, its presence as a private university to provide opportunities for all generations of nations of different races, tribes and religions to continue their education, UNW Mataram has the obligation to pay attention to multicultural matters in this university so that it is intertwined peace and success for the entire academic community. This study shows that the implementation of multicultural education at UNW Mataram runs well by adopting an inclusive learning approach, Enriching the curriculum with multicultural issues, Supporting and facilitating multicultural activities and organizations, Building partnerships or MOUs with government agencies, as well as private and universities within the region and abroad.